1991
DOI: 10.1007/bf02265153
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane of trout spermatozoa: I. Isolation and partial characterization

Abstract: AbslractThe plasma membrane from spermatozoa of rainbow trout was isolated by four techniques: sonication, hypotonic shock, mechanical homogenization after freeze-thawing, and nitrogen cavitation, in combination with continuous sucrose gradient centrifugation. Nitrogen cavitation (900 PSI, 20 min equilibration at 4°C) was the most effective technique.Following nitrogen cavitation, four bands were recovered in the sucrose gradient at densities = 1.03, 1.05, 1.09 and 1.15 g/ml. Elect ron microscopy revealed memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, except for these ionic and water channels, there are still many types of membrane proteins unidentified in fish. Labbé and Loir (1991) isolated membrane proteins from spermatozoa of rainbow trout (O. mykiss) by four techniques (sonication, hypotonic shock, mechanical homogenisation after freeze-thawing, and nitrogen cavitation, in combination with continuous sucrose gradient centrifugation) and showed that most of the membrane proteins (with 42-and 30-kDa bands as the main proteins) were acidic to neutral.…”
Section: Membrane Proteinsmentioning
confidence: 99%
“…However, except for these ionic and water channels, there are still many types of membrane proteins unidentified in fish. Labbé and Loir (1991) isolated membrane proteins from spermatozoa of rainbow trout (O. mykiss) by four techniques (sonication, hypotonic shock, mechanical homogenisation after freeze-thawing, and nitrogen cavitation, in combination with continuous sucrose gradient centrifugation) and showed that most of the membrane proteins (with 42-and 30-kDa bands as the main proteins) were acidic to neutral.…”
Section: Membrane Proteinsmentioning
confidence: 99%
“…Plasma membrane extraction from sperm was carried out following an adapted protocol from de Curtis et al [40] and Labbé and Loir [41]. For total sperm, activated and nonactivated spermatozoa were recovered as above; homogenized in a buffer containing 20 mM Tris-HCl (pH 7.8), 3 mM MgCl 2 , 0.25 M sucrose, and protease inhibitors; and centrifuged at 1000 3 g for 20 min at 48C.…”
Section: Plasma Membrane Purification Of Intact Spermatozoa Head Anmentioning
confidence: 99%
“…Aliquots of sl-PC and sl-SM in chloroform were dried and resuspended by vigorous vortexing with SpM at 48C; 7.2 nmol of labeled lipid in SpM was added to the cell pellet containing about 2 3 10 9 sperm cells. Considering a membrane phospholipid content of about 375 nmol per 10 9 cells [51], the molar concentrations of sl-PC and sl-SM in the trout sperm membrane were about 1%. After 5 min at 188C, cells were washed by addition of 20 volumes SpM and then were centrifuged.…”
Section: Characterization Of Membrane Fluidity By Spin-labeled Lipidsmentioning
confidence: 99%